From police training to police educator: the role of the police in the formation of the citizen and in the construction of a democratic (Research, Society and Development, 2022)
This article analyzes the relationship and possible practical consequences of public and social investments in police education and how much this training contributes to the role of the police officer as an educator. In the text, initially, the theme of police redemocratization is examined, the possible causes of violence and inefficiency of public security in Brazil, regarding the application of human rights, the unpreparedness of security agents and their lack of technical-scientific qualification. for the achievement of its attributions and the financial decline of the States. The causes of police inefficiency/efficiency and the need to unify the police are analyzed, which despite the changes in the conduct of public security agents, there are still insensitive police officers, whose attitude reflects in ill-treatment of citizens. Finally, it discusses the importance of police education for its effective performance as a police educator. The text emphasizes that it is up to the police officer to also act as an educator and assist in the formation of citizens, to contribute to the evolution of institutions, to develop an ethical conscience of respect for fundamental Human Rights and, above all, to work for the transformation and consolidation of a democratic society.